Impact of social determinants and medical mistrust on parent-child HPV vaccination in economically disadvantaged communities: implications for cancer prevention - Marcelo M. Sleiman; Mary Rose Yockel; Mingqian Liu; Joanne Wendolowski; Lucile L. Adams-Campbell; Chiranjeev Dash; Lisa Carter-Bawa; Abraham Aragones; Sahana Arumani; Kenneth P. Tercyak (Frontiers in Oncology)
IntroductionHuman papillomavirus (HPV) vaccination and intentions, their correlates, and barriers among age-eligible parents and their children living in very economically disadvantaged communities were assessed.MethodsParents (N=198; 45% Black, 42% Latine, 57% educated <=high school [HS], 74% income <$60k annually) with children ages 10-17 from Washington, DC and Hackensack, NJ were intercepted at community events and surveyed.ResultsAmong age-eligible parents, 20% were vaccinated against HPV. Comparing vaccinated to unvaccinated parents, those who were non-white (OR=5.5, 95% CI=3.5, 9.4, p<0.001) and with unvaccinated children (OR=8.9, 95% CI=3.7, 23.3, p<0.001) were less likely to be vaccinated themselves. Among children, 37% were vaccinated. Unvaccinated children were more likely to have parents who were non-white (OR=2.7, 95% CI=2.6, 2.8, p<.01), with a <=HS education (OR=3.0, 95% CI=1.52, 6.25, p<.01), and were unvaccinated themselves (OR=10.2, 95% CI=4.01, 28.61, p<.001). Nearly two-thirds (63%) of parents with unvaccinated children expressed an intention to vaccinate within the next year: 48% confirmed receiving advice from a healthcare provider to do so. Common HPV vaccine barriers included lack of information (35%), safety concerns (16%), and perceptions of sexual inactivity (13%). An adjusted model revealed an interaction between parent education and medical mistrust (B=.35, SE=.13, 95% CI=0.09, 0.61, p<.01). For parents with <=HS education, when levels of provider trust were strong, they were more open to vaccinating their children.ConclusionsHPV vaccine prevalence was low among parents and children living in disadvantaged communities. Comprehensive education and intervention to build trust are warranted to prevent the spread of HPV-linked cancers and reduce cancer disparities.